Pengaruh Kohesivitas Kelompok dan Self Efficacy Terhadap Social Loafing pada Anggota Organisasi Kedaerahan di Lingkungan Uin Syarif Hidayatullah Jakarta - Aulia, Hilya; Saloom, Gazi (TAZKIYA Journal of Psychology, 2013)
Social loafing defined as the tendency to reduce in motivation and effort that occurs whenindividuals work collectively in groups than when they work individually. The main purposeof this article is to know the effect of group cohesiveness, self-efficacy, gender, and age on socialloafing. Total sample was 150 respondents from members of regional organizationparticipated in this research. Measuring instrument consists of social loafing refers toChidambaram & Tung (2005), scale of group cohesiveness use group environmentquestionnaire (GEQ) developed by Widmeyer, Brawley, and Carron (1985) and self efficacyrefers to Bandura (1986).The result of this study indicte group cohesiveness and self efficacyhave significant effecr on social loafing. Specifically, individual attraction to the group-social(ATG-S), individual attraction to the group-task (ATG-T) and the magnitude significantlyinfluence to social loafing.